LEADERSHIP RESPOND TO ORGANIZATIONAL CHANGE RESISTANCE - Louis Mokolensang; Charles Henry S Tangkau; Wilson Bogar (SEIKO : Journal of Management & Business, 2020)
This study aims to describe the analysis, and interpret the leadership style of the Sukur Village Chief Airmadidi District, North Minahasa Regency. The method of approach uses qualitative or postpositivistic, because it is considered appropriate according to the problem at hand. The results of the research obtained by the Lurah in communicating are still not open, many decisions are not conveyed to his employees transparently and the Lurah's weak ability to communicate both with employees and the community. Good communication will have an impact on the preparation of work program planning which is a further action after determining the vision organization; Experience in the world of government is still minimal with a background of junior high school teachers and educational qualifications not in the field of government and the village head does not understand the vision and mission of the village organization; The Lurah does not really understand the main tasks and does not yet have a work program planning and Lurah's inhospitability in decision making is dominated by the character of his past and his reluctance to practice according to existing rules. The ability of the lurah in understanding the existing resistance either personally to the rules or resistance to problems related to decision making has not yet implemented the existing rules and is more dominated by what is not desired by the rules, understanding the rules there but to practice those which are still not maximal, especially in in his decision-making which is dominated by his feelings and delegation of tasks that do not understand Job description according to the duties that are owned, so that the problem solving in this study The need for rolling positions based on expertise and competence; Commitment to the involvement and participation of the Lurah needs to be increased; Positioning a Lurah must Understand the Auth and rules; Assignment of tasks based on task fields and competencies; Background The Lurah must meet educational qualifications, skills and loyalty